Right Care, First Time: Developing a Theory-Based Automated Protocol to Help Clinically Stage Young People Based on Severity and Persistence of Mental Illness - Iorfino, Frank; Cheng, Vanessa Wan Sze; Cross, Shane P.; Yee, Hannah F.; Davenport, Tracey A.; Scott, Elizabeth M.; Hickie, Ian B. (Frontiers in Public Health, 2021)
The bulk of mental disorders emerge before the age of 25 years and, if left untreated, have the potential to lead to considerable lifetime burden of disease. The technological implementation of clinical staging for youth mental health can assist the early detection and treatment of mental disorders. We describe the development of a theory-based automated protocol to facilitate the initial clinical staging process, its intended use, and strategies for protocol validation and refinement. While this protocol has the potential to be adapted to incorporate different psychometric measures and additional biopsychosocial dimensions, each subsequent adaptation must be validated. Robust medicolegal and ethical guidelines must also be established to guide the analysis and potentially ongoing collection of this multidimensional data. Regardless, this theory-based automated protocol represents a step forward towards technology-enabled, personalised delivery of mental health care.